Types of High-Performance Liquid Chromatography (HPLC) Columns: A Review - Natashya Evangeline Fiorelia; Anthony Dharma Wibowo; Natanael Leonard Lae; Allison Ang; Oki Krisbianto (FoodTech: Jurnal Teknologi Pangan, 2022)
Some chemical analysts, especially those working in the food sector, often find it difficult to choose the HPLC columns for their research. Every so often they tend to modify their method to fit whatever HPLC column available in their laboratory instead of looking for the column type best suited to their experiments. Other than that, HPLC column types are often very limited discussed in the class. This is particularly disadvantageous for those who have sufficient access to select the HPLC column they need for the best result. The lack of insight into the types of HPLC columns available in the market also influenced their decision to select the right column in their analysis to a large extent. This article briefly reviews the differences between the commonly used Particle-Packed Columns with the newer yet less frequently used Monolithic Columns. The types of HPLC columns based on polarity, molecular size, and the electrical charge will be described further, along with the working principle of the columns in brief and various examples of options available on the market. Lastly, the uses of HPLC columns in the food industries are also described. This review is expected to contribute to the field of chemical analysis, such as food analysis.